การพัฒนาหนังสืออิเล็กทรอนิกส์ในการป้องกันการติดเชื้อเอชไอวี สำหรับกลุ่มชายที่มีเพศสัมพันธ์กับชาย - ศรีสกุล สังกำปัง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
HIV infection is increasing among men who have sex with men (MSM) because of their sexual risk behaviors. The aim of this study was to develop an HIV prevention electronic book for men who have sex with men. This study was conducted from October 2014 to January 2015 and included 42 MSM who were members of a foundation in Chiang Mai province. The research instruments included a development and design plan for the electronic book, an electronic book user opinion questionnaire, a demographic data questionnaire, an HIV knowledge test, and an electronic book satisfaction questionnaire. Data were analyzed using descriptive statistics. The electronic book developed for this study included sections on HIV, mode of transmission, incidence and prevalence, impact, risk behaviors, safe sex, and post-exposure prevention for sexual exposure with risky partners. The efficiency of the electronic book was 80.50/81.67 higher than assigned efficiency criteria (80/80). User satisfaction was high for content (4.33-4.50), design (3.96-4.36), and usability (4.33-4.40). The results of the study show that the developed electronic book on HIV prevention among men who have sex with men is efficient and may be used to increase knowledge on HIV prevention among MSM.